A method for preparing a graphene composite material uniformly loaded with nanoparticles

CN118183862BActive Publication Date: 2026-10-30LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410431672.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2026-10-30
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

[0005]然而,上述方法中为恢复石墨烯的良导体作用采用还原的手段,可能会影响纳米粒子的特性(还原过程中,随着温度的升高,纳米粒子因小尺寸效应所具备的高热导率会降低以及晶粒尺寸会生长),且存在繁琐的步骤,不利于石墨烯纳米粒子制备技术的规模化推广

Benefits of technology

[0021]本发明通过高压(600~1500MPa)实现石墨烯与纳米粒子团聚体的充分解离,从而促进石墨烯表界面缺陷位点与纳米粒子的静电吸附作用,进而完成纳米粒子在石墨烯表面的均匀负载。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118183862B_ABST
    Figure CN118183862B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a graphene composite material uniformly loaded with nanoparticles, and belongs to the technical field of carbon materials.The application provides a preparation method of a graphene composite material uniformly loaded with nanoparticles, and comprises the following steps: mixing graphene, nanoparticles and a liquid-phase dispersant, and performing a closed high-pressure homogenization treatment to obtain the graphene composite material uniformly loaded with nanoparticles; the pressure of the closed high-pressure homogenization treatment is 600-1500 MPa.The application realizes the full dissociation of the graphene and the nanoparticle agglomerates through high pressure (600-1500 MPa), thereby promoting the electrostatic adsorption of the graphene surface interface defect sites and the nanoparticles, and then completing the uniform loading of the nanoparticles on the graphene surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon materials technology, specifically relating to a method for preparing a graphene composite material with uniformly loaded nanoparticles. Background Technology

[0002] Nanomaterials are composed of tiny units equivalent to or even atomic sizes, possessing unique physical or chemical properties that distinguish them from other materials formed from the same chemical elements. These properties include mechanical, electrical, magnetic, and thermal characteristics, as well as surface effects, small-size effects, quantum size effects, and macroscopic quantum tunneling effects. These characteristics make nanomaterials extremely promising for applications in new energy, biomedicine, microwave absorption, and heavy metal adsorption.

[0003] The tendency of nanomaterials to aggregate has always been a key factor limiting their performance. Utilizing the large specific surface area of ​​graphene as a matrix for nanomaterials is currently the main solution to improve the aggregation problem. Traditional methods for loading nanomaterials onto graphene, such as ultrasonic stirring, chemical co-precipitation, solvothermal methods, and high-temperature reduction, cannot effectively solve the problem of easy aggregation of graphene and nanoparticles.

[0004] The most common approach is to utilize the abundant oxidized functional groups on the surface of graphene oxide, a graphene precursor, as reaction sites. This is achieved through the electrostatic adsorption of nanoparticles by the functional groups, resulting in uniform loading of nanoparticles on the graphene surface. The graphene structure is then restored through reduction, thus achieving uniform loading of nanoparticles on the graphene surface.

[0005] However, the reduction method used in the above method to restore the good conductor effect of graphene may affect the properties of nanoparticles (during the reduction process, as the temperature increases, the high thermal conductivity of nanoparticles due to their small size effect will decrease and the grain size will grow), and there are cumbersome steps involved, which is not conducive to the large-scale promotion of graphene nanoparticle preparation technology. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a method for preparing graphene composite materials with uniformly loaded nanoparticles. The preparation method provided by this invention can achieve uniform loading of nanoparticles on the graphene surface without affecting the properties of the nanoparticles; at the same time, the preparation method is simple and has prospects for industrial application.

[0007] To achieve the above objectives, the present invention provides the following solution:

[0008] This invention provides a method for preparing a graphene composite material with uniformly loaded nanoparticles, comprising the following steps:

[0009] Graphene, nanoparticles and liquid dispersant are mixed and subjected to closed high-pressure homogenization treatment to obtain a graphene composite material with uniformly loaded nanoparticles.

[0010] The pressure of the closed high-pressure homogenization process is 600-1500 MPa.

[0011] Preferably, the pressure of the closed high-pressure homogenization process is increased in a stepwise manner.

[0012] Preferably, the closed-loop high-pressure homogenization process includes: adjusting the high pressure to 800-1000 MPa for the first homogenization; after the first homogenization, adjusting the high pressure to 900-1100 MPa for the second homogenization; after the second homogenization, raising the high pressure to 1000-1200 MPa for the third homogenization; after the third homogenization, raising the high pressure to 1100-1300 MPa for the fourth homogenization; after the fourth homogenization, raising the high pressure to 1200-1400 MPa for the fifth homogenization; and after the fifth homogenization, raising the high pressure to 1300-1500 MPa for the sixth homogenization, for a total of 6 times.

[0013] Preferably, the nanoparticles include one or more of metal oxide nanoparticles, metal nitride nanoparticles, metal nanoparticles, and non-metal-based nanoparticles.

[0014] Preferably, the mass ratio of graphene to nanoparticles is (1-10):(1-10); the total mass of graphene and nanoparticles to the volume ratio of liquid dispersant is (1-10) mg:(1-100) mL.

[0015] Preferably, the grain size of the nanoparticles is <500 nm.

[0016] Preferably, the total time for the closed high-pressure homogenization process is 30 min to 3 h.

[0017] Preferably, after completing the closed high-pressure homogenization process, the product is further dried.

[0018] Preferably, the drying process includes freeze drying, low-temperature vacuum drying, or carbon dioxide drying.

[0019] Preferably, the drying temperature is -60 to 40°C and the drying time is 24 to 72 hours.

[0020] This invention provides a method for preparing a graphene composite material uniformly loaded with nanoparticles, comprising the following steps: mixing graphene, nanoparticles and a liquid dispersant, and subjecting the mixture to a closed high-pressure homogenization treatment to obtain a graphene composite material uniformly loaded with nanoparticles; wherein the pressure of the closed high-pressure homogenization treatment is 600-1500 MPa.

[0021] This invention achieves full dissociation of graphene and nanoparticle aggregates by applying high pressure (600-1500 MPa), thereby promoting the electrostatic adsorption of nanoparticles at the graphene surface defect sites and thus completing the uniform loading of nanoparticles on the graphene surface.

[0022] This invention applies pressure to a liquid confined within a limited, enclosed space, generating strong shear, impact, and cavitation effects. This forces the nanoparticle aggregates and graphene to effectively dissociate, disperse, and refine. Furthermore, in this invention, the graphene material, within the narrow cavity and high-pressure environment, is subjected to the impact of water pressure and airflow, along with accompanying thermal effects (in the background art, the temperature during reduction is stable and continuously rising, and the reduction of nanoparticles at high temperatures generally requires a relatively constant temperature environment to achieve the small size effect of nanocrystals; however, the thermal effect in this invention involves a brief temperature increase followed by a return to the initial state). This alters the structural morphology of the graphene, causing not only the internal expansion of the graphene aggregates but also tearing of the graphene structure and an increase in surface defect sites. This results in a richer number of interaction sites at the graphene surface, which electrostatically interact with the nanoparticles in the simultaneously dissociated, free environment, achieving uniform loading of the nanomaterial. The preparation method provided by this invention, by not using reduction methods, does not affect the properties of the nanoparticles.

[0023] This invention utilizes a simple liquid-phase high-pressure method to achieve uniform dispersion and loading of graphene and nanoparticles in one step. Since graphene is used directly as the raw material without subsequent processing steps, it greatly saves time and energy costs, making it a preparation method with promising industrial applications. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 The image shows a scanning electron microscope (SEM) image of the final product, graphene-based carbonyl iron nanocomposite material, obtained after six homogenization processes in Example 1.

[0026] Figure 2 Here is a scanning electron microscope image of carbonyl iron from Example 1;

[0027] Figure 3 This is a scanning electron microscope image of the final product, graphene-based cobalt trioxide nanocomposite material, obtained after six homogenization cycles in Example 2.

[0028] Figure 4 This is a scanning electron microscope image of the graphene-based cobalt trioxide nanocomposite material of Comparative Example 1. Detailed Implementation

[0029] This invention provides a method for preparing a graphene composite material with uniformly loaded nanoparticles, comprising the following steps:

[0030] Graphene, nanoparticles, and a liquid dispersant were mixed and subjected to closed-loop high-pressure homogenization to obtain a graphene composite material with uniformly loaded nanoparticles.

[0031] Unless otherwise specified, the materials and equipment of this invention are commercially available.

[0032] In this invention, the method for preparing the graphene includes one or more of the following: solid-phase mechanical exfoliation, liquid-phase mechanical exfoliation, electrochemical exfoliation, and chemical intercalation-expansion exfoliation. This invention does not impose any particular requirements on the preparation steps of the solid-phase mechanical exfoliation, liquid-phase mechanical exfoliation, electrochemical exfoliation, and chemical intercalation-expansion exfoliation methods; steps well-known in the art can be used.

[0033] In this invention, the nanoparticles preferably include one or more of the following: metal oxide nanoparticles, metal nitride nanoparticles, metal nanoparticles, and non-metal-based nanoparticles; the metal oxide nanoparticles preferably include one or more of the following: nano-zinc oxide, nano-alumina, nano-cerium oxide, carbonyl iron, and nano-iron oxide; the metal nitride nanoparticles preferably include one or more of the following: nano-titanium nitride, nano-zirconium nitride, nano-magnesium nitride, and nano-lithium nitride; the metal nanoparticles preferably include one or more of the following: nano-silver, nano-copper, nano-iron, and nano-gold; and the non-metal-based nanoparticles preferably include one or more of the following: silicon tetroxide nanoceramics, polyaniline nanopolymers, and nano-silica composite materials. In this invention, the grain size of the nanoparticles is preferably <500 nm, more preferably 10–100 nm.

[0034] In this invention, the preferred mass ratio of graphene to nanoparticles is (1-10):(1-10), more preferably (1-5):(1-5), and even more preferably (2-4):(2-4); the preferred volume ratio of the total mass of graphene and nanoparticles to the liquid dispersant is (1-10) mg:(1-100) mL, more preferably (2-8) mg:(5-50) mL.

[0035] In this invention, the liquid dispersant preferably comprises water and / or an organic solvent; the organic solvent preferably comprises one or more of ethanol, acetone, and ethylene glycol. When the liquid dispersant comprises both water and an organic solvent, this invention does not have any particular requirements on the ratio of water to organic solvent, and a ratio well known in the art can be used.

[0036] In this invention, the equipment used for the closed high-pressure homogenization process preferably includes a high-pressure homogenizer, a high-pressure emulsifying shearing machine, or a micro-jet homogenizer.

[0037] In this invention, the pressure of the closed high-pressure homogenization treatment is 600-1500 MPa; the total time of the closed high-pressure homogenization treatment is preferably 30 min-3 h, more preferably 1-2.5 h, and even more preferably 1-1.5 h.

[0038] In this invention, the pressure of the closed high-pressure homogenization process is preferably increased in a stepwise manner. Specifically, the high pressure is adjusted to 800-1000 MPa for the first homogenization; after the first homogenization, the high pressure is adjusted to 900-1100 MPa for the second homogenization; after the second homogenization, the high pressure is increased to 1000-1200 MPa for the third homogenization; after the third homogenization, the high pressure is increased to 1100-1300 MPa for the fourth homogenization; after the fourth homogenization, the high pressure is increased to 1200-1400 MPa for the fifth homogenization; after the fifth homogenization, the high pressure is increased to 1300-1500 MPa for the sixth homogenization, for a total of 6 times. In this invention, the time for the first, second, third, fourth, fifth, and sixth homogenizations is 15 minutes.

[0039] This invention utilizes a stepped pressure increase method to protect the equipment used in the sealed high-pressure homogenization process from clogging. Furthermore, the higher the pressure, the smaller the nanoparticles are pulverized, resulting in better homogenization. The gradient pressure increase allows for the gradual refinement of nanoparticles. 。

[0040] This invention achieves full dissociation of graphene and nanoparticle aggregates by applying high pressure (600-1500 MPa), thereby promoting the electrostatic adsorption of nanoparticles at the graphene surface defect sites and thus completing the uniform loading of nanoparticles on the graphene surface.

[0041] After completing the closed high-pressure homogenization process, the present invention preferably further includes drying the resulting product.

[0042] In this invention, the drying process preferably includes freeze drying, low-temperature vacuum drying, or carbon dioxide drying; the drying temperature is preferably -60 to 40°C, more preferably -40 to 20°C, and even more preferably -20 to 10°C; the drying time is preferably 24 to 72 hours, more preferably 30 to 60 hours, and even more preferably 40 to 50 hours.

[0043] This invention removes the solvent through freeze-drying, low-temperature vacuum drying, or carbon dioxide drying to prevent changes in the interlayer spacing of the graphene assembly (graphene assembly refers to the composite of intercalated graphene and nanoparticles, with nanoparticles uniformly loaded and penetrating between the intercalated graphene).

[0044] This invention applies pressure to a liquid confined within a limited, enclosed space, generating strong shear, impact, and cavitation effects. This forces the nanoparticle aggregates and graphene to effectively dissociate, disperse, and refine. Furthermore, in this invention, the graphene material, within a narrow cavity and under high pressure, is subjected to the impact of water pressure and airflow, along with the accompanying thermal effects. This alters the graphene's structural morphology, causing not only the internal expansion of the graphene aggregates but also tearing of the graphene structure and an increase in surface defect sites. Consequently, the graphene surface and interface form more abundant interaction sites, which electrostatically interact with the nanoparticles in the simultaneously fully dissociated free environment, achieving uniform loading of the nanomaterials.

[0045] The preparation method provided by this invention does not use reduction methods and therefore does not affect the properties of the nanoparticles.

[0046] This invention utilizes a simple liquid-phase high-pressure method to achieve uniform dispersion and loading of graphene and nanoparticles in one step. Since graphene is used directly as the raw material without subsequent processing steps, it greatly saves time and energy costs, making it a preparation method with promising industrial applications.

[0047] To further illustrate the present invention, the preparation method of a graphene composite material with uniformly loaded nanoparticles provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0048] Example 1

[0049] Graphene was prepared by a bubble-triggered exfoliation method (chemical intercalation expansion exfoliation method): 1 g of 325 mesh graphite powder (purchased from Maclean's Reagent Co., Ltd.) was weighed into a 50 mL beaker. 20 mL of concentrated sulfuric acid (purchased from Maclean's Reagent Co., Ltd.) was added to the beaker containing 1 g of 325 mesh graphite powder. The mixture was stirred evenly with a glass rod. 4 mL of hydrogen peroxide (purchased from Maclean's Reagent Co., Ltd.) was added dropwise to the beaker. The mixture was allowed to stand for 24 h, washed with distilled water until neutral, and then placed in a freeze dryer to dry for 48 h to obtain intercalated graphene.

[0050] Preparation of graphene carbonyl iron nanocomposite material: Weigh 4 mg of the intercalated graphene and 2 mg of carbonyl iron ( Figure 2 (Scanning electron microscopy image of carbonyl iron) Add the sample to 200 mL of distilled water and place it in a high-pressure homogenizer. Adjust the pressure to 900 MPa for the first homogenization, and the time for the first homogenization is 15 min. After the first homogenization, adjust the pressure to 1000 MPa for the second homogenization, and the time for the second homogenization is 15 min. After the second sample homogenization, increase the pressure to 1100 MPa for the third homogenization, and the time for the third homogenization is 15 min. After the third sample homogenization is completed... The pressure was increased to 1200 MPa for a fourth homogenization, which lasted 15 minutes. After the fourth homogenization, the pressure was increased to 1300 MPa for a fifth homogenization, which also lasted 15 minutes. After the fifth homogenization, the pressure was increased to 1400 MPa for a sixth homogenization, which also lasted 15 minutes. A total of six homogenizations were performed. The resulting liquid was then placed in a freeze dryer and dried at -60°C for 72 hours to obtain the graphene carbonyl iron composite material.

[0051] Figure 1 The images show scanning electron microscope (SEM) images of the final product, graphene-based carbonyl iron nanocomposite material, obtained after six homogenization cycles in Example 1. The images are shown at different positions and magnifications. The scale bars are as follows: First row, first image: 0.2 μm, second image (middle): 100 nm, third image: 100 nm; Second row, first image: 50 nm, second image (middle): 100 nm, third image: 0.2 μm. As can be seen from the images, the high-pressure homogenization method can further pulverize and refine the carbonyl iron nanoparticles, allowing them to be uniformly loaded onto the graphene surface.

[0052] Example 2

[0053] Graphene was prepared by electrochemical exfoliation: a 75 wt% aqueous solution of lithium bis(trifluoromethanesulfonyl)imide was used as the electrolyte, graphite was used as the anode and a platinum sheet was used as the cathode. The anode and cathode were connected to a DC power supply with a distance of 6 cm between the two electrodes. A voltage of 20 V was applied, and the intercalation expansion at 28 °C lasted for 2.5 h without electrode exfoliation, resulting in graphene aggregates. After vacuum filtration and cleaning, water was added, and the aggregates were dispersed in a 120 W ultrasonic cleaner for 60 min to obtain a 1 mg / mL graphene dispersion. The dispersion was dried at -20 °C under a vacuum of 20 Pa for 72 h to obtain graphene powder (EG).

[0054] Preparation of cobalt trioxide nanomaterials: 1.9 g of cobalt hexahydrate and cobalt chloride (purchased from Maclean's Reagent Co., Ltd.) and 0.8 g of sodium hydroxide (purchased from Maclean's Reagent Co., Ltd.) were added to 160 mL of deionized water and stirred until the solid particles were completely dissolved. The mixture was then transferred to a Teflon-lined stainless steel autoclave and reacted solvothermically at 120 °C for 3 h. The product was washed three times with ethanol and distilled water, and then dried in a vacuum oven at 60 °C for 4 h. The prepared cobalt hydroxide nanosheets were placed in a tube furnace and heat-treated in air at 290 °C for 2 h to obtain cobalt trioxide nanosheets.

[0055] Preparation of graphene-cobalt trioxide nanocomposite material: Weigh 4 mg of the graphene powder (EG) and 2 mg of the cobalt trioxide nanosheets, add them together to 200 mL of distilled water, and place them in a high-pressure homogenizer. Adjust the high pressure to 900 MPa for the first homogenization, and the first homogenization time is 15 min. After the first homogenization, increase the high pressure to 1000 MPa for the second homogenization, and the second homogenization time is 15 min. After the second homogenization, increase the high pressure to 11000 MPa for the second homogenization. The pressure was increased to 1200 MPa for a third homogenization, lasting 15 minutes. After the third homogenization, the pressure was increased to 1200 MPa for a fourth homogenization, also lasting 15 minutes. After the fourth homogenization, the pressure was increased to 1300 MPa for a fifth homogenization, also lasting 15 minutes. After the fifth homogenization, the pressure was increased to 1400 MPa for a sixth homogenization, lasting 15 minutes, for a total of six homogenizations. The resulting liquid was then freeze-dried at -60°C for 72 hours to prepare the graphene-cobalt trioxide nanocomposite material.

[0056] Figure 3 The images show scanning electron microscope (SEM) images of the final product, graphene-based cobalt trioxide nanocomposite material, obtained after six homogenization cycles in Example 2. The images are taken at different positions and magnifications. As can be seen from the images, the high-pressure homogenization method can uniformly load cobalt trioxide nanoparticles onto the graphene surface.

[0057] Example 3

[0058] Graphene was prepared by liquid-phase mechanical exfoliation: 5g of 50-mesh graphite powder was added to 500mL of N-methylpyrrolidone (NMP) solution, and mechanical exfoliation was performed using a high-speed shear machine at 1100rpm for 12h. After shearing, a graphene solution was obtained. Incompletely exfoliated graphite sheets were removed by centrifugation at 2500rpm for 5min. Then, the liquid-phase mechanically exfoliated graphene nanosheets (GNPs) were collected by centrifugation at 10000rpm for 30min and vacuum dried for 72h to obtain GNPs powder.

[0059] Preparation of graphene-silver nanocomposite material: Weigh 4 mg of the aforementioned GNPs powder and 2 mg of silver nanoparticles (purchased from Aladdin Co., Ltd.), add them together to 200 mL of distilled water, and place them in a high-pressure homogenizer. Adjust the pressure to 900 MPa for the first homogenization, and the first homogenization time is 15 min. After the first homogenization, adjust the pressure to 1000 MPa for the second homogenization, and the second homogenization time is 15 min. After the second homogenization, increase the pressure to 1100 MPa for the third homogenization, and the third homogenization time is 15 min. After the third homogenization, increase the pressure to 1200 MPa for the fourth homogenization, and the fourth homogenization time is 15 min. After the fourth homogenization, increase the pressure to 1300 MPa for the fifth homogenization, and the fifth homogenization time is 15 min. After the fifth homogenization, increase the pressure to 1400 MPa for the sixth homogenization, and the sixth homogenization time is 15 min, for a total of 6 homogenizations. After six cycles, the liquid was placed in a freeze dryer and dried at -60°C for 72 hours to prepare graphene-silver nanocomposite material.

[0060] Comparative Example 1

[0061] The preparation steps for graphene powder (EG) and cobalt trioxide nanomaterials are the same as in Example 2;

[0062] Preparation of graphene-cobalt trioxide nanocomposite material: Weigh 4 mg of EG and 2 mg of cobalt trioxide nanomaterial, add them together to 200 mL of distilled water, place them in an ultrasonic cleaner and sonicate for 120 min at a power of 120 W. Place the sonicated solution in a freeze dryer for 72 h to obtain graphene-cobalt trioxide nanocomposite material.

[0063] Figure 4 The image shows a scanning electron microscope (SEM) image of the graphene-based cobalt trioxide nanocomposite material of Comparative Example 1. As can be seen from the image, the graphene-cobalt trioxide nanocomposite material prepared by ultrasonic dispersion has a large nanoparticle size and severe agglomeration, making it impossible to uniformly load it onto the graphene surface.

[0064] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphene composite material with uniformly loaded nanoparticles, characterized in that, Includes the following steps: Graphene, nanoparticles, and a liquid dispersant are mixed and subjected to closed-loop high-pressure homogenization to obtain a graphene composite material with uniformly loaded nanoparticles; the liquid dispersant is water and / or an organic solvent. The pressure of the closed high-pressure homogenization process is 600~1500MPa; The pressure of the closed high-pressure homogenization process is increased in a stepwise manner. The closed high-pressure homogenization process includes: adjusting the high pressure to 800~1000MPa and performing the first homogenization; After the first homogenization is completed, the high pressure is adjusted to 900~1100MPa for the second homogenization; after the second homogenization is completed, the high pressure is increased to 1000~1200MPa for the third homogenization; after the third homogenization is completed, the high pressure is increased to 1100~1300MPa for the fourth homogenization; after the fourth homogenization is completed, the high pressure is increased to 1200~1400MPa for the fifth homogenization; after the fifth homogenization is completed, the high pressure is increased to 1300~1500MPa for the sixth homogenization, for a total of 6 homogenizations.

2. The preparation method according to claim 1, characterized in that, The nanoparticles include one or more of the following: metal oxide nanoparticles, metal nitride nanoparticles, metal nanoparticles, and non-metal-based nanoparticles.

3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of graphene to nanoparticles is (1~10):(1~10); the total mass of graphene and nanoparticles to the volume ratio of liquid dispersant is (1~10) mg:(1~100) mL.

4. The preparation method according to claim 1 or 2, characterized in that, The grain size of the nanoparticles is <500 nm.

5. The preparation method according to claim 1, characterized in that, The total time for the closed high-pressure homogenization process is 30 min to 3 h.

6. The preparation method according to claim 1, characterized in that, After completing the closed high-pressure homogenization process, the product is then dried.

7. The preparation method according to claim 6, characterized in that, The drying process includes low-temperature vacuum drying or carbon dioxide drying.

8. The preparation method according to claim 7, characterized in that, The drying temperature is -60~40℃, and the time is 24~72h.

Citation Information

Patent Citations

  • Preparation method of graphene / CoFe2O4 composite nano magnetic solid lubricant

    CN110129108A